S6 Long term lung function outcomes in children born with abdominal wall defects. (14th November 2013) - Rajalingam, S; Mok, Q; Curry, J; Eaton,; Fettes, E; Kirkby, J; Aurora, P
Abstract : Introduction: Although survival following surgical repair of abdominal wall defect is now good, there are very few data regarding long-term lung function (LF) outcomes. The aim of this study was to describe LF at school-age for a post-surgery population from a single large centre. Methods: All children having surgical repair of exomphalos or gastroschisis between 1/1/1998 30/6/2007 at our institution were identified, and those aged greater than 6 years were recalled for LF testing. Children born with major associated cardiac, genetic or laryngeal conditions were excluded from the study. All children underwent resting oximetry, body plethysmography, forced spirometry and carbon monoxide transfer test. Clinical and demographic data was also collected. Results were converted to z-scores to adjust for height, sex, age and ethnicity. Statistical comparisons between groups were performed with t-tests. Results: 86 children were approached and LF data were obtained in 31 (12 Exomphalos;19 Gastroschisis) children aged ≥ 6 years. 22 children were male; the mean age at testing was 9.9 years (range: 6.4 14.4). When analysed as a group these children had significantly reduced forced expiratory volumes in 1s, FEV1 ( -0.52 z-scores [95%CI -1.01, -0.04] p = 0.036), FEV1 /FVC (-0.88 [-1.21, -0.56] p < 0.000), lung transfer factor, TLCO (-0.76 [-1.05, -0.47] p < 0.000), TLCO /VA (-1.77 [-2.08, -1.46] p < 0.000), functional residual capacity, FRC (-0.45 [-0.70, -0.19] p = 0.001), residual volume, RV (-0.36 [-0.61, -0.12] p = 0.006) and significantly increased alveolar volume, VA (0.95 [0.37, 1.53] p = 0.002). Forced vital capacity, FVC was normal (-0.01 [-0.54, 0.51] p = 0.96) When analysed as subgroups, children post exomphalos repair had significantly lower LF than those post gastroschisis repair, with a mean difference (95% CI of difference [Exomphalos Gastroschisis] ) in FEV1 of -1.52 z-scores (-2.35, -0.68; p = 0.001); FVC -1.54 (-2.47, -0.62; p = 0.002); TLC -0.91 (-1.78, -0.04; p = 0.041). No significant group differences were found in the remaining lung function outcomes. Conclusions: This is the largest study to report lung function at school-age in children post abdominal wall surgery. We demonstrate that these children have significantly reduced lung function; and when analysed by subgroup, that those with a history of exomphalos repair have significantly greater defect than those with a history of gastroschisis repair.